Structural basis for small molecule targeting of Doublecortin Like Kinase 1 with DCLK1-IN-1 - Onisha Patel (Nature Portfolio, 2021)
Patel et al. report crystal structures of the kinase domain of Doublecortin-like kinase 1 (DCLK1) in complex with a potent inhibitor and its precursors. Their structural study reveals insights into the mode of action of the inhibitor DCLK1-IN-1 and sets the basis for the design of isoform-specific inhibitors of DCLK1, which plays a role in tumour growth and development.